LEGAL PROTECTION OF THE RIGHTS OF WIVES IN DIVORCE CASES IN RELIGIOUS COURTS ACCORDING TO SUPREME COURT REGULATION NUMBER 3 OF 2017 - Thariq Athila Liandi; Lailatus Sururiyah (Inspiring Law Journal, 2026)
Marriage according to law is an innate bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on the one Godhead. Separation or divorce is an attempt to release the bond of husband and wife from a marriage caused by certain reasons. Divorce occurs because there is no way out. Seeing the many injustices received by the wife who filed a divorce lawsuit because she did not get her rights again after the divorce. The Supreme Court issued Supreme Court Regulation Number 3 of 2017, this regulation is present as a legal instrument that provides greater space for judges in the Religious Courts to uphold substantive justice and protect the rights of women, including wives in divorce cases.The type of research used in this thesis is normative legal research. This normative legal research method is a research method that focuses on the study of applicable legal norms or rules. This method is often used in research in the field of law or other sciences related to certain norms or rules.The results of this study show that the Protection of Wife's Rights in Divorce Cases in Religious Courts shows that Supreme Court Regulation Number 3 of 2017 can provide legal certainty in the form of iddah alimony and alimony that is still provided by the male party even though the divorce lawsuit comes from the woman. The main obstacle lies in the inconsistency of judges' interpretation of substantive justice due to the lack of gender sensitivity training. low public awareness of these rights. In addition, the legal consequences of the husband who does not carry out this order are subject to sanctions on the husband, namely administrative sanctions imposed on the husband who does not carry out this regulation after the divorce from the wife.